Practical bank management - Toft, Kenneth (Plymouth : Macdonald and Evans, 1977)
In this book you will read little about technical skills. The book is concerned with the art and skills of management and how these can be applied in the banking context.
Includes index.
osc 22/01/2019
Loans
Keywords: Bank management